A New Species of the Genus Acrossocheilus Oshima, 1919 (Cypriniformes: Cyprinidae) from the Dabie Mountains - Tian-En Chen; Jia-Xin Xu; Peng-Ju Li; Huan-Fu Hu; Kai Gao; Hai-Peng Zhao (Animals)
Acrossocheilus Oshima, 1919, a cyprinid genus of Cyprinidae in southern China and currently comprises 26 valid species. In this study, we describe Acrossocheilus dabieensis sp. nov. from the Dabie Mountains, China. This new species differs from its congeners by the following combination of characters: The second primary vertical bar (PB2) is situated beneath the anterior origin of the dorsal fin in females and subadult males. Vertical bars extend to the end of the ventral abdomen in juveniles, and they gradually recede above the lateral line in adult females, whereas they are absent in adult males. The last unbranched dorsal-fin ray is slender with a smooth posterior margin. Phylogenetic analyses based on the mitochondrial DNA sequences indicate that A. dabieensis sp. nov. is a monophyletic group, and it forms a sister group with A. kreyenbergii, reinforcing the status of the new species. A key to the barred species of Acrossocheilus is also provided.